Legal Protection for Underage Rape Victims Who Experience Forced Marriage With The Perpetarator - Tristan, Jose; Muhammad Azil Maskur (Universitas Negeri Semarang, 2025)
Forced marriage, particularly involving underage victims of sexual violence, remains a pressing issue in Indonesia’s legal and human rights landscape. Despite the enactment of Law No. 12 of 2022 on Sexual Violence Crimes, which criminalizes forced and child marriage—including those justified by cultural traditions—challenges persist in enforcement and victim protection. This study examines the legal safeguards available to child rape victims forced into marriage with their perpetrators, evaluates the effectiveness of Indonesia’s legal system in addressing sexual violence, and explores necessary legal reforms to enhance justice for survivors. By applying a normative descriptive approach, this research identifies gaps in policy, law enforcement, and institutional support, emphasizing the need for stronger victim protection mechanisms, law enforcement consistency, and multi-sector collaboration to ensure comprehensive recovery and justice